Mao Zedong sixiangde guanghui yongyuan puzhao zuguo dadi -relie gingzhu <Mao Zedong xuanji> diwu quan chuban - Ma Jindong,
'The radiance of Mao Zedong Thought eternally illuminates all of the nation -warmly celebrate the publication of the fifth volume of the 'Selected Works of Mao Zedong'. Printno. 8073.10212.